Cutting ability of the flexofile instrument in resin simulated canals - de Medeiros, João Marcelo Ferreira; Zöllner, Nivaldo André; de Carvalho, Pedro Luiz; Rosifini Alves, Ana Paula [UNESP]; Pires Clemente, Rosana Giovanni (My University, 2008)
The purpose of this investigation was to compare cutting ability of a Flexofile instruments in substrate phenolic resin simulated canals blocks before and after the root canal preparation using two techniques, one were a hand instrumentation technique and the other, a engine-driven rotatory motion (Endo-Gripper). Twenty simulated canals manufactured in resin blocks were divided two groups, the first one hand technique (G1) and the second one, a rotatory motion instrumentation (G2) being the blocks weight difference of the groups before and after the instrumentation. The results were showed no statistically significant differences between the two types of instrumentation techniques (manual and rotatory) regarding the cutting ability (p=0,05).
Capacidad de corte de la lima flexofile en canales simulados
Keywords: Dental instruments; Endodontics; Instrumentation; Methods